Emotional competencies and psychological well-being of educational science professionals: integrating quantitative and qualitative methods - Oyarzún Gómez, Denise; Dauvin Herrera, Cristóbal; Eguia Elias, Cesar (Frontiers in Education, 2025)
ObjectiveIn the post-pandemic context, positive mental health indicators for professionals working in schools have not been frequently researched. This study's principal objective is to determine the relationship between emotional competencies and psychological well-being among educational science professionals enrolled in continuing education programs during the post-pandemic period in Chile. A secondary objective is to describe the qualitative perceptions of the relationship between emotional competencies and psychological well-being in this sample of Chilean professionals.MethodA mixed convergent, non-experimental, cross-sectional approach was used. The initial phase was quantitative, correlational, and comparative, while the subsequent phase was qualitative, exploratory, and descriptive. The sample consisted of 193 educational science professionals, with an average age of 38.56 years (SD = 8.52), including 61.7% of women. Participants completed an online questionnaire that featured the Emotional Competencies Inventory for Adults (ICEA), Scale of Psychological Well-being (SPWB), open-ended questions, and sociodemographic data. Scale reliability, descriptive statistics, Pearson's correlation, and t-tests for mean differences were performed for analysis. Qualitative data were examined through thematic analysis, which identified codes and themes to enrich the quantitative findings.ResultsValidity evidence was reported for the ICEA and SPWB. The findings revealed a connection between emotional competencies and psychological well-being. Differences in emotional regulation and positive relationships were observed, favoring women. Other educational science professionals achieved higher average scores in emotional awareness, which was qualitatively described as a process of personal transformation. Teachers demonstrated elevated levels of emotional autonomy and personal growth. Qualitative accounts indicated that recognizing strengths and weaknesses facilitated personal growth and improvement. It was found that professionals in virtual programs attained higher scores for ICEA, autonomy, and emotional regulation.ConclusionThis research adds to the growing body of evidence supporting the relationship between emotional competencies and psychological well-being. Its specific contribution focused on professionals currently enrolled in postgraduate programs while working in schools. The findings provide insights to inform the design of policies and training practices that foster the comprehensive development of these professionals in the post-pandemic context.